Uncovering the hidden value of citizen beach clean-ups: a social media–based assessment in Spain - Pablo Otero; Eva Cacabelos; Joana Ferreira; Patricia Pérez; Jesús Gago (Marine Pollution Bulletin, 2026)

Concomitant effects of algae invasion and sea urchin mass mortality drive the shift from barrens to turf grounds - Alejandro Bernal-Ibáñez; Jordi Boada; Eva Cacabelos; Marta Florido-Capilla; Raül Triay-Portella; Patrício Ramalhosa; Rodrigo P. Silva; João Canning-Clode; Ignacio Gestoso (Marine Environmental Research, 2026)

Variation in species composition and evenness drive long-term changes in the structure of rocky shore communities - Afonso C.L. Prestes; Ana I. Neto; Eva Cacabelos; Gustavo M. Martins (Marine Environmental Research, 2025)

Entangled ecosystems: the impact of macroplastic litter on Mytilus galloprovincialis communities in northwestern Spain - Jacob Houvener; Ignacio Moreu; Eva Cacabelos; Ignacio Gestoso; Jose M. F. Babarro; Mark Lenz (Frontiers in Marine Science, 2025)
Plastic litter in the ocean has gained significant attention over recent decades, with much of the focus on microplastics. However, macroplastic litter is prevalent in marine environments, and while its effects on single organisms is well documented, its effects on community-level biological structures remain poorly understood. This study investigates the impact of macroplastic litter—specifically polyethylene film (shopping bags) and nylon filament (fishing line)—on Mytilus galloprovincialis aggregates and their associated fauna in the Ría de Vigo, NW Spain. Using a fully factorial experimental design, 30-mussel aggregates were assembled incorporating plastic litter in different abundances and were deployed in situ for 4 weeks. After this time, physiological responses (respiration and filtration), structural complexity (rugosity index), particulate matter retention, body condition index (BCI), and associated mobile faunal diversity were measured. Mussels in the High/Filament treatment showed an 18% lower respiration rate and a 65% reduction in filtration capacity compared to controls, while the Low/Filament treatment reduced filtration by 40%. No significant effects were found on BCI, particulate retention as well as on the diversity and composition of the associated macrofauna. Interestingly, aggregates with low plastic content exhibited a slightly higher structural complexity than those with high amounts of plastic. This study highlights that macroplastics can subtly alter the functionality of mussel beds without dramatically affecting the diversity of the associated fauna. These insights underscore the need to assess physical interactions of organisms with plastic litter also at the community level.

The spread of Aoroides longimerus Ren & Zheng, 1996 across the Mediterranean and the Atlantic: genetic diversity, anthropogenic transport, and ecological implications - JOSÉ MANUEL GUERRA-GARCÍA; ANDREA DESIDERATO; SERENA MUCCIOLO; CARLOS NAVARRO-BARRANCO; MACARENA ROS; JASMINE FERRARIO; PAULA MORETTI; AGNESE MARCHINI; NAWFEL MOSBAHI; SOFÍA RUIZ-VELASCO; IGNACIO GESTOSO; PATRÍCIO RAMALHOSA; et al. (Mediterranean Marine Science, 2025)
Accurate knowledge of the global distribution of non-indigenous species (NIS) is essential for understanding their invasion dynamics and for implementing timely management measures. This study reports the first records of the marine amphipod Aoroides longimerus, putatively native to the East Asian coast, in Italy (2018), Spain (2019) and Tunisia (2022) and provides the earliest documented record of the species in its introduced European range (Portugal, 2011). Furthermore, it expands the species’ known distribution in mainland Portugal (including the northernmost record), Macaronesia (with first records in the Canary Islands and Madeira), and confirms its presence along the Atlantic coasts of France and the Netherlands. Aquaculture facilities, particularly those associated with oyster farming, are probably the primary vector of introduction, while recreational boating may have contributed significantly to secondary dispersal. In comparison to other exotic amphipods, A. longimerus remains absent from many marinas, ports and/or aquaculture facilities in the Mediterranean Sea and adjacent regions, such as the Red Sea. This suggests that the species may still be in the early stages of expansion, or that its dispersal ability across marinas and ports is more limited than that of other amphipods. The present study, however, highlights several key ecological traits of A. longimerus: (i) it can survive year-round despite seasonal fluctuations, and reach high local densities, (ii) it exhibits strong colonisation capacity, as shown by its rapid establishment on settlement plates, and (iii) it displays opportunistic feeding behaviour, primarily consuming detritus. These characteristics underscore the importance of continuous surveillance and effective communication with stakeholders to prevent further expansion of this species.

Surface integrity could limit the potential of concrete as a bio-enhanced material in the marine environment - Juan Sempere-Valverde; Sahar Chebaane; Alejandro Bernal-Ibáñez; Rodrigo Silva; Eva Cacabelos; Patrício Ramalhosa; Jesús Jiménez; João Gama Monteiro; Free Espinosa; Carlos Navarro-Barranco; José Manuel Guerra-García; João Canning-Clode (Marine Pollution Bulletin, 2024)

Identification of potential invasive alien species in Spain through horizon scanning - Carlos Cano-Barbacil; Martina Carrete; Pilar Castro-Díez; Miguel Delibes-Mateos; Josep A. Jaques; Marta López-Darias; Manuel Nogales; Joan Pino; Macarena Ros; Anna Traveset; Xavier Turon; Montserrat Vilà; et al. (Journal of Environmental Management, 2023)

Testing differences of marine non-indigenous species diversity across Macaronesia using a standardised approach - Nuno Castro; Ignacio Gestoso; Patrício Ramalhosa; Evandro Lopes; Corrine Almeida; Ana Costa; Manuela Parente; Eva Cacabelos; Rogélio Herrera; José L. Costa; João Canning-Clode (Marine Pollution Bulletin, 2023)

Location and building material determine fouling assemblages within marinas: A case study in Madeira Island (NE Atlantic, Portugal) - Juan Sempere-Valverde; Patrício Ramalhosa; Sahar Chebaane; Free Espinosa; João Gama Monteiro; Alejandro Bernal-Ibáñez; Eva Cacabelos; Ignacio Gestoso; José Manuel Guerra-García; João Canning-Clode (Marine Pollution Bulletin, 2023)

Monitoring Non-Indigenous Species with Passive Sampling Methods in an Oceanic Island - Anna Diem; Patrício Ramalhosa; Eva Cacabelos; Jasmine Ferrario; Nuno Castro; Filipe Henriques; João Gama Monteiro; Paula Chainho; Christopher Kim Pham; João Canning-Clode; José Paula; Ignacio Gestoso (Journal of Marine Science and Engineering, 2023)
The synergistic effects of biological invasions have long been considered significant causes of biodiversity loss worldwide. Therefore, early detection monitoring is crucial in mitigating nonindigenous species (NIS) threats. In the marine environment, settlement plates were used as monitoring devices in ports, but this method was mainly applied to assess the sessile benthic community and is less efficient in collecting the mobile biota and accessing its diversity. Moreover, as the potential expansion of NIS to the surrounding coastal environment is still poorly understood, a pilot study was conducted focusing on two aspects: (i) improving the feasibility of the settling method under different environmental contexts and (ii) enhancing the capacity of the developed prototypes to collect more representative samples (i.e., sessile and mobile biota). Three different prototypes were designed: a box prototype consisting of PVC plates encapsulated by a plastic bottle, a CD prototype with CDs surrounded by a net, and a PVC prototype with uncovered PVC plates. The prototypes were deployed inside a marina and in an outside area on Madeira Island, Portugal. Results indicate that the PVC prototype was the most efficient regarding monitoring the sessile community, whereas the box prototype showed the highest abundance of the mobile fauna. The location influenced both the sessile community composition and the number of mobile taxa. Our findings suggest combining features from prototypes to encompass the whole benthic community better.

Role of non-indigenous species in structuring benthic communities after fragmentation events: an experimental approach - Eva Cacabelos; Ignacio Gestoso; Patrício Ramalhosa; João Canning-Clode (Biological Invasions, 2022)

The collapse of marine forests: drastic reduction in populations of the family Sargassaceae in Madeira Island (NE Atlantic) - Alejandro Bernal-Ibáñez; Ignacio Gestoso; Peter Wirtz; Manfred Kaufmann; Ester A. Serrão; João Canning-Clode; Eva Cacabelos (Regional Environmental Change, 2021)
Species of the genera Cystoseira , Ericaria , Gongolaria , and Sargassum (family Sargassaceae) are key components of the Mediterranean-Atlantic marine forests, essential for biodiversity and ecosystem functioning. Populations of these foundational species are particularly vulnerable to anthropogenic impacts, likely to be intensified under future scenarios of climate change. The decline and even disappearance of these species have been reported in different areas of the world. At Madeira Island (NE Atlantic), populations of Gongolaria abies-marina , Ericaria selaginoides , Sargassum vulgare , and Sargassum filipendula , the most ecologically relevant species in Macaronesian marine forests, have been suffering a drastic decline during the last decades, especially on the southern coast of the island, where anthropogenic pressure is higher than on the north coast. The lack of sufficient temporal coverage on qualitative and quantitative studies of Sargassaceae communities in Madeira poses a challenge to establish a specific period for this decline. Consulting qualitative studies and historical records, we have set for the first time a timeline that shows an evident decrease in Sargassaceae populations in the last 20 years on Madeira Island. Following this timeline, we pinpoint the start of this decline in the first decade of the 2000s. This can be particularly confirmed for places like Funchal and Reis Magos, with significantly higher historical records. Currently, most benthic communities on shallow subtidal rocky reefs along the south coast are dominated by sea urchins and crustose coralline algae, the so-called sea urchin barrens. However, in some cases, they are entirely covered by a layer of sediment. We discuss the possible factors contributing to these drastic changes, bringing Madeira’s marine forests to a dramatic decline. As many animal species rely on marine forests, the decline of Sargassaceae populations represents an invaluable ecological loss for the coastal ecosystem of the island.

The Role of Sea-Urchins in Marine Forests From Azores, Webbnesia, and Cabo Verde: Human Pressures, Climate-Change Effects and Restoration Opportunities - Alejandro Bernal-Ibáñez; Eva Cacabelos; Ricardo Melo; Ignacio Gestoso (Frontiers in Marine Science, 2021)
Marine forests ecosystems are typical of temperate rocky benthic areas. These systems are formed by canopy-forming macroalgae (Laminariales, Tilopteridales, and Fucales) of high ecological value that provide numerous ecosystem services. These key species are also indicators of good environmental status. In recent decades, marine forests have been threatened by different impacts of local and global origin, putting their stability and survival in question. On a global scale, in many temperate areas of the planet, marine forests have been replaced by “sea-urchins barrens.” We present a general overview of sea-urchins’ population status in the archipelagos of Azores, Webbnesia (Madeira, Selvagens, and Canary Islands) and Cabo Verde, focusing on their role in the maintenance of the so-called “alternate stable state.” After an in-depth evaluation of the different anthropogenic and environmental pressures, we conclude that sea-urchins population explosion has been facilitated in the benthic habitats of Madeira and Canary Islands, preventing the recovery of canopy-forming macroalgae assemblages and being one of the main drivers in maintaining a stable barren state. Diadema africanum is the main barrens-forming species in Webbnesia, where it reaches high densities and strongly impacts macroalgal assemblages. On the other hand, in the most pristine areas, such as the Selvagens Islands and other Marine Protected Areas from the Canary Islands, the density of D. africanum is up to 65% lower than in the nearby Madeira Island, and macroalgal communities are preserved in good status. This information is critical for marine environmental management, highlighting the urgent need for implementation of appropriate control mechanisms and restoration actions headed to the conservation of marine forests in Macaronesian archipelagos.

Limited effects of marine protected areas on the distribution of invasive species, despite positive effects on diversity in shallow-water marine communities - Eva Cacabelos; Gustavo M. Martins; João Faria; Afonso C. L. Prestes; Tarso Costa; Ignacio Moreu; Ana I. Neto (Biological Invasions, 2020)

Intertidal assemblages across boulders and rocky platforms: a multi-scaled approach in a subtropical island - Eva Cacabelos; Ignacio Gestoso; Patrício Ramalhosa; Léa Riera; Ana I. Neto; João Canning-Clode (Marine Biodiversity, 2019)

Do Non-Indigenous Species (NIS) prevailing over native species with climate change effects? - Nuno Castro; João Canning-Clode; Patrício Ramalhosa; Eva Cacabelos; José Lino Costa; Ignácio Gestoso (Frontiers in Marine Science, 2019)

Biofilms shaping compositions of macrofouling assemblages: An initial barrier against NIS settlement? - Eva Cacabelos; Patrício Ramalhosa; João Canning-Clode; Jesus Troncoso; Celia Olabarria; Cristina Delgado; Sergey Dobretsov; Ignacio Gestoso (Frontiers in Marine Science, 2019)

A new methodology for the study of biological invasions on coastal communities - Ignacio Gestoso; Patrício Ramalhosa; Eva Cacabelos; Jasmine Ferrario; Nuno Castro; João Monteiro; Paula Chainho; Christopher Pham; João Castro; João Canning-Clode (Frontiers in Marine Science, 2019)

Material type and roughness influence structure of inter‐tidal communities on coastal defenses - Eva Cacabelos; Gustavo M. Martins; Richard Thompson; Afonso C. L. Prestes; José Manuel N. Azevedo; Ana I. Neto (Marine Ecology, 2016)
On a global scale, urbanization has resulted in substantial proportions of coasts being replaced by artificial structures such as marinas, breakwaters and seawalls. There is broad consensus that coastal defense structures are poor surrogates of the natural habitats that they replace. Here we investigated the effects of the type and roughness of materials used for the construction of artificial structures on the surrounding biota by comparing abundances and distribution of key inter‐tidal taxa between natural shores and coastal defenses. Lower abundances of gastropods and barnacles were found on artificial coastal defense structures (regardless of the material type). At small spatial scales, abundances of key taxa increased with increasing roughness. Our results suggest that the choice of materials used for the construction of coastal defense structures has little effect on community structure per se , but that enhanced roughness could make coastal defenses better surrogates of natural habitats by supporting assemblages that are more similar to those found on natural shores.

Aggregated and dispersed configuration of microhabitats in coastal defenses: Implications for restoration of populations - Cacabelos Eva; Martins Gustavo; Moniz Isadora; Thompson Richard; Prestes Afonso; Azevedo José; Neto Ana (Frontiers in Marine Science, 2014)